Feasibility Study Shows Multicenter, Observational Case-Control Study Is Practicable to Determine Risk of Secondary Breast Cancer in Females With Differentiated Thyroid Carcinoma Given Radioiodine Therapy in Their Childhood or Adolescence; Findings Also Suggest Possible Fertility Impairment in Such Patients - Drozd, Valentina; Schneider, Rita; Platonova, Tamara; Panasiuk, Galina; Leonova, Tatjana; Oculevich, Nataliya; Shimanskaja, Irina; Vershenya, Irina; Dedovich, Tatjana; Mitjukova, Tatjana; Grelle, Inge; Biko, Johannes; et al. (Frontiers in Endocrinology, 2020)
Objective: This single-center, observational case-control feasibility study sought to test key elements of a protocol for an eventual long-term international observational case-control study of a larger patient cohort, to evaluate the risk of breast cancer as a second primary malignancy in females with differentiated thyroid cancer (DTC) given radioiodine therapy (RAI) during childhood or adolescence. Patients: Females developing DTC after the Chernobyl accident in Belarus and ≤19 years old at the time of thyroid surgery were enrolled: patients given RAI (n = 111) and controls of similar age not given RAI (n = 90). Results: One case of breast cancer was newly diagnosed among the RAI patients, but none in controls. Patients given RAI significantly less frequently needed 2nd surgeries than did controls (23%, 26/111 vs. 39%, 35/90, P < 0.05); the main indication for such procedures usually is suspicion of local recurrence. RAI patients appeared to have had more frequent reproductive difficulties than did controls: 78% (87/111) of the former vs. 93% (84/90) of the latter had a history of pregnancy (P < 0.01), and the mean number of pregnancies was 1.5 ± 1.2 in RAI patients vs. 1.9±1.1 in controls (P < 0.05). Most notably, infertility was observed in 23% (26/111) of RAI patients vs. 4% (4/90) of controls (P < 0.01). In conclusion, a international observational case-control study on breast cancer after DTC in patients given RAI vs. not given RAI appears to be feasible. Additional research and everyday clinical attention should be devoted to reproductive function after RAI in young females.